Pengelolaan Pendidikan Non Formal (Studi Kasus Pada Pengajian Alfurqon Sibuhuan) - Siregar, Irma Suryani (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2023)
This study aims to analyze the management of Sibuhuan's al-Furqon recitation. As we know, Sibuhuan Padang Lawas as a religious society makes Islamic education a priority for the community and students. Besides that, there are also many other non-formal education in the midst of society. It is important to study the management of al-Furqon recitation as a non-formal educational institution that is very beneficial to society. This research is a qualitative research with a descriptive analysis approach. Data collection was carried out by observation, in-depth interviews and documentation, using the Miles and Huberman model of data analysis techniques. The findings of this study indicate that Al-Furqon Study is a non-formal education that provides free education for the community, with specifications for the introduction of hijaiyah letters, makhroj lessons, tajwid and recitations of the Qur'an, besides that there are also additional learning materials, such as monotheism and jurisprudence and morals, the learning process of which is carried out every day after the evening prayer until 9 pm.